The Effect of the Use of Synthetic Mesh Soaked in Antibiotic Solution on the Rate of Graft Infection in Ventral Hernias: A Prospective Randomized Study - Yabanoğlu, Hakan (Int Surg, 2015)
Wound infections and seroma formations are important problems in ventral hernia repair operations using synthetic mesh grafts. The aim of this study was to investigate the effect of the use of synthetic mesh soaked in vancomycin solution on the rate of graft infection. The total number of subjects was 52. The subjects were randomized into 2 groups using a software program. Group 1 (n = 26) was the control group. In group 2 (n = 26), synthetic mesh was soaked in a Vancomycin solution before it was implanted. The patients were compared with respect to demographic characteristics and preoperative, intraoperative, and postoperative variables. There were no significant differences between the groups with respect to the available variables. Seroma development was significantly more common in group 2 (P < 0.041). Three patients (5.7%) developed superficial wound infection, and 9 (17%) developed surgical site infection 2–type wound-site infection. No significant difference was found between the groups in terms of infection. The use of synthetic mesh soaked in vancomycin solution had no beneficial effects on the rate of wound-site infection. Future randomized, controlled, large-scale studies using the same mesh and suture types, and meshes soaked in larger spectrum antibiotics are needed.